Development of pythagorean theorem worksheets based on realistic mathematics education to facilitate students' mathematical reasoning ability - Maya Aulia Putri; Elfis Suanto; Susda Heleni (Jurnal Absis: Jurnal Pendidikan Matematika dan Matematika, 2026)
This study was motivated by students’ low mathematical reasoning ability, particularly in the geometry topic of the Pythagorean theorem. The 2022 PISA results also indicate that Indonesian students’ mathematical performance remains relatively low, partly due to learning practices that emphasize memorization and provide limited non-routine problems that support reasoning. Therefore, this study aimed to develop Pythagorean theorem worksheets based on Realistic Mathematics Education (RME) to facilitate students’ mathematical reasoning ability. This research employed a Research and Development (R&D) design using the 4-D development model, consisting of define, design, develop, and disseminate stages. The product was developed for eighth-grade students and was validated by three expert validators. Product trials were conducted through one-to-one evaluation involving three students, a small group trial involving six students, and a field trial involving 34 students at SMPN 8 Pekanbaru. The instruments used were validation sheets and student practicality questionnaires. The results showed that the developed worksheets obtained an average validation score of 4.40, categorized as very valid. The practicality test obtained an average score of 3.48 in the small group trial and 3.48 in the field trial, both categorized as very practical. These findings indicate that the RME-based Pythagorean theorem worksheets are valid and practical for use as teaching materials to facilitate students’ mathematical reasoning ability.